Comparison of Compression and Noncompression Forearm Sleeve On Grip Muscle Strength In Badminton Players - Anggriani, Atika Febri; Ihwanul Muhlishin, Rohmat; Sisybania (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background: Badminton players need good grip muscle strength to hit the ball while playing. Muscle strength can be increased by training and using forearm sleeves. There are two types of forearm sleeves, namely compression forearm sleeves and non-compression forearm sleeves. Both types differ in the materials used. The compression type has polyamide material, and the non-compression type has polyester material. Both have different elasticity. Elasticity affects the compression of the muscles. The more elastic a material is, the more it will compress. Purpose: to find out whether there is a difference in the use of compression forearm sleeves and non-compression forearm sleeves on grip muscle strength in badminton players. Method: This research method is quasi experimental with a two group pretest posttest design. The population in this study was 40 with a total sample of 22 players taken using purposive sampling techniques according to the predetermined inclusion and exclusion criteria. Results: This test used a paired t-test and obtained a p value of 0.000 for the compression type with an average difference of 1 with an increase of 4.6%. The non-compression group used the Wilcoxon test with a p value of 0.003. Has an average difference of 0.5909 with an increase of 2%. Conclusion: The use of compression forearm sleeves is better for increasing grip muscle strength in badminton players than the use of non-compression forearm sleeves.